Advocacy for Monitoring and Evaluation in Community Development Projects in Africa - Maithya, Paul M (Advances in Social Sciences Research Journal, 2014)
Much of retrospection and reassessment of past undertakings and activities is necessary so to gain confidence in future tasks and ensure success. Review is mandatory and important in development projects. Many projects and programs suffer losses because of lack of or inefficient and ineffective monitoring and evaluation. Monitoring and evaluation helps in identifying the problem before hand or in time, hence, taking precautionary and even corrective measures in time. To win the favour of the donors and creditors, the evidence that the projects and programmes initiated are succeeding is inevitable. The type of evaluation depends on the object being evaluated and the purpose of the evaluation. Monitoring and evaluation should be incorporated in the planning of a project or programme. The monitoring and evaluation process may be presented in several phases. Methodology adopted was review of literature and the conclusions were made based on arguments elicited in the paper. Key Words: monitoring; evaluation; community; development; project; Africa